Problems of social and economic development of Ukrainian cities in the regional economy system : financial dominants - Babukh, Ilona (Baltija Publishing, 2025)
Financial support for local self-government is an integral part of sustainable development of territorial communities, which determines the effectiveness of resource management at the local level. In the face of dynamic changes, including war, decentralization is increasingly important, as it allows local authorities to increase their financial autonomy. However, this requires optimizing budget planning, attracting investments, and expanding the revenue base of communities. State transfers remain an important tool in this process, helping to balance the financial capacity of different regions, especially in times of crisis. The fiscal decentralization reform implemented before the war significantly strengthened the financial capacity of local budgets, but the war led to a temporary centralization of budget resources. In such circumstances, utilities play a critical role, facing financial difficulties due to outdated infrastructure and unregulated tariffs. To ensure the sustainability of these enterprises, budget funding is needed, as well as the effective use of grant resources and international technical assistance. The development of infrastructure and social initiatives requires the introduction of various financing mechanisms, such as local borrowing and investment. Restoration and improvement of decentralization in the post-war period should take into account new socio-economic challenges and meet European standards. The key task is to strengthen the financial self-sufficiency of territorial communities, which will help reduce their dependence on centralized transfers. Improving inter-budgetary relations and effective management of budgetary resources are important components of the country's economic recovery after the war